Technology Adoption Factors for Supreme Audit Institutions - Ceki, Babalwa; Moloi, Tankiso (Journal of Accounting Research, Organization and Economics, 2024)
Objective Arguably, there is a shortage of research on how supreme audit institutions can use cutting-edge technologies to make them more effective and stay up with the evolving audit landscape as we are in the 4IR age. Professional auditing and accounting groups encourage using cutting-edge technologies in accounting and auditing duties. However, public sector auditing is trailing behind in the digital transition. Guidelines regarding the elements that superior audit institutions must consider when implementing cutting-edge technologies are still required. This paper fills the gap in the literature by providing technology adoption factors that have been verified for usefulness and practicability and then evaluated in order of significance by experts from eight different countries. Therefore, the findings and recommendations of the paper are applicable and relevant on a global scale.Design/Methodology Experts were consulted to validate and rate the importance and practicability of the variables and processes for technology adoption using two Delphi questionnaires.Results The technology adoption factors identified were assistance from top management, a plan for embracing technology, and fostering an environment focused on digital culture. Assessing the current systems for compliance with legislation, organization-wide preparation, and the ability to incorporate new technology, ongoing staff training, regulatory compliance, environmental policies, and audit standards are necessary. Evaluating the technology's compatibility and complexity, doing a cost-benefit analysis, and determining whether the auditee platforms are ready for advanced technology auditing were rated as important technology adoption factors by experts.